The Microstructure and hardness properties of ZrO2+Y 2O3/Al2O3 layers coated by using plasma spray process on Al bronze surface - Özel, Serkan; Turnan, Hüseyin (Carl Hanser Verlag, 2010)
In this study, ZrO2 + Y2O3/Al 2O3 powders were coated on the surface of aluminum bronze (Cu + 5 % Al) by using the atmospheric plasma spraying method. The effect of Al2O3 on microstructure and hardness was examined in four different coatings applied by using 5-10-20 % Al2O3 ratio in ZrO2 + Y2O3 and ZrO2 + Y 2O3. For this purpose, microstructure images of the coated layers were taken in optical microscope and SEM, EDX and XRD analyses were performed and their microhardness values were measured. It was observed that a porous structure occurred in the coatings containing ZrO2 + Y 2O3ZAl2O3. The coatings containing Al2O3 showed higher microhardness values than the one without Al2O3, and depending on the increase of Al 2O3 amount, the amount of porosity increased and microhardness value decreased. © Carl Hanser Verlag, München.
Mikrostruktur und Härte von ZrO2+Y2O 3/Al2O3-Schichten, die mit dem Plasmaspritzverfahren auf eine Oberfläche aus Aluminiumbronze aufgebracht wurden
Keywords: Aluminum; Aluminum alloys; Bronze; Coatings; Hardness; Microhardness; Microstructure; Plasma jets; Plasma spraying; Porosity; Zirconium alloys; Al bronze; Aluminum bronze; Atmospheric plasma spraying; Coated layers; Plasma spray process; Porous structures; XRD analysis; Aluminum coatings